Flotation behavior and mechanism of ilmenite using ferrate as activator. (15th March 2022) - Liao, Runpeng; Wen, Shuming; Liu, Jian; Zuo, Qi; Zheng, Yongxing; Luo, Deqiang
Graphical abstract: Highlights: A novel activation reagent for ilmenite flotation was proposed. Na2 FeO4 was used as a surfactant to change the valence state of Fe on the ilmenite surface. Na2 FeO4 increased the active sites on the surface for collector interaction/adsoption. Fe 3+ content significantly increased, and sodium oleate readily interacted with Fe 3+ . Abstract: The activation property of ferrate on the flotation of ilmenite using sodium oleate as collector was studied in this work. Flotation tests reveal that the sodium ferrate strongly activated ilmenite at a pH range from 5 to 10. The addition of sodium ferrate increases ilmenite's surface active sites and enhances the interaction with sodium oleate. The recovery of ilmenite can be increased from 62% to more than 90% at pH 6. After ferrate treatment, the surface Zeta potential of ilmenite becomes more positive, and the isoelectric point (IEP) increases from pH 5.5 to pH 7.2. In the sodium oleate system, the Zeta potential becomes more negative after sodium ferrate treatment from pH 5 to 9. Reaction thermodynamic analysis shows that oleate ion is easier to adsorb with Fe(III) species on the surface of ilmenite at pH 6. The results of Fourier-transform infrared spectroscopy (FT-IR) analysis show that more active sites of metal ions are formed on the surface of ilmenite after sodium ferrate treatment. X-ray photoelectron spectroscopy (XPS) test shows that after ferrate treatment in the collector system, the Fe2p3 content on the surface of ilmenite increases from 2.15% to 3.37%, and the Fe(III) content increases from 19.81% to 33.34%, which makes it easier for sodium oleate to adsorb with ilmenite chemically. The addition of sodium ferrate makes ilmenite's surface have more Fe(III) active sites, which helps improve the flotation recovery of ilmenite.